163 Nice: neoantigen-cytokine-chemokine multifunctional engager for NK cell immunotherapy of solid tumors. (9th November 2020) - Yao, Xue; Matosevic, Sandro
Abstract : Background: The effectiveness of natural killer cell-based immunotherapy against solid tumors is limited by the lack of specific antigens and the immunosuppressive tumor microenvironment. To improve the clinical efficacy and specificity of NK cell therapy, we are designing, developing, and characterizing a new generation of multi-specific killer engagers, which consists of a neoantigen-targeting moiety, together with cytokine and chemokine-producing domains. Methods: Targeting a neoantigen-an antigen formed specifically in response to tumor genome mutations-enables substantially enhanced tumor specificity to be achieved. We evaluated the responsiveness of NK cells to Wilms Tumor 1 (WT1) antigen in GBM by synthesizing an antibody that is able to recognize the WT1/HLA complex. Incorporation of cytokine (namely IL-2, IL-15, and IL-21)-essential for the maturation, persistence, and expansion of NK cells in vivo-favors the proliferation and survival of NK cells in the tumor microenvironment, thereby leading to more sustained anti-tumor responses. Additionally, our data have indicated that the chemokine CXCL10 plays an important role in the infiltration of immune cells into GBM, yet the chemokine itself is expressed at low levels in GBM. Incorporation of a CXCL10-producing element into our construct further supports NK cell recruitment and may stimulate the recruitment of other immune cells. NK activation through the tri-specific engager is achieved through NKp46-mediated signaling. We are investigating the ability of the tri-functional engager to support and enhance NK cell-mediated cytotoxicity against GBM in vitro and in patient-derived GBM xenografts in vivo. Results: We hypothesize that taking advantage of our multi-functional engager, NK cells will exhibit, at once, superior persistence, infiltration and antitumor activity, simultaneously addressing three of the main limitations to the use of NK cells in immunotherapy of GBM and other solid tumors. Conclusions: N/A Acknowledgements: N/A